Workplace misconduct and the requirement of due inquiry: with reference to the practice in Malaysia - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig; Ahmad, Muhamad Hassan; Ramalingam, Chithra Latha; RV Rajan, R Usha Devi (LexisNexis Malaysia Sdn Bhd, 2019)
This paper discusses the concept of workplace misconduct and the requirement of a domestic or due inquiry to establish the alleged act and with reference to the practice in Malaysia. The issues considered herein are as follows: (a) whether the disciplinary or domestic inquiry is essential in an impending dismissal for alleged gross misconduct; and (b) whether the dismissal carried out without convening a disciplinary inquiry violates the principles of natural justice thereby rendering the dismissal unfair.